Capital Market Reaction to News and Policies Regarding Covid-19 in Indonesia: Event Study Method - Yuana, Pusvita; Alhamda Prasetya, Yunan (DINASTI RESEARCH, 2025)
This study examines the reaction of the Indonesian capital market to Covid-19-related news and policies during 2020–2021, focusing on abnormal stock returns and value fluctuations. Using an event study methodology, market reactions to significant events were analyzed. The sample comprised 603 companies listed on the Indonesia Stock Exchange, selected through purposive sampling. Abnormal returns were assessed within event windows: 21-day periods (t-10 to t+10) for Events 1, 2, and 3; 11-day periods (t-5 to t+5) for Events 4 and 6; and a 16-day period (t-10 to t+5) for Event 5. Data included the combined stock price index and daily closing prices aligned with event windows. A one-sample t-test identified significant changes in abnormal returns. The findings reveal abnormal returns and significant value fluctuations, with hypothesis testing showing varied market reactions across windows. However, no consistent reaction pattern emerged, reflecting the unpredictable nature of investor behavior during the pandemic. The results align with the semi-strong form of the Efficient Market Hypothesis (EMH), demonstrating rapid incorporation of public information but highlighting anomalies driven by uncertainty, sectoral differences, and event-specific impacts. This study contributes to understanding financial market behavior during global crises.